Meditation and its benefits - Magdalena Wójcik; Grzegorz Boreński; Julita Poleszak; Przemysław Szabat; Marta Szabat; Joanna Milanowska (Journal of Education, Health and Sport, 2019)
Introduction: Meditation can include any kind of practices during practitioners can calm their mind and expend their consciousness. Meditation practising have been known since a long time ago. However, in the West it is still gaining popularity since nowadays people are under more and more stress. Meditation is thought to be helpful in coping with chronic disorders or stress.